If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9.2 = 0.2x + 2.4 Reorder the terms: -9.2 = 2.4 + 0.2x Solving -9.2 = 2.4 + 0.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.2x' to each side of the equation. -9.2 + -0.2x = 2.4 + 0.2x + -0.2x Combine like terms: 0.2x + -0.2x = 0.0 -9.2 + -0.2x = 2.4 + 0.0 -9.2 + -0.2x = 2.4 Add '9.2' to each side of the equation. -9.2 + 9.2 + -0.2x = 2.4 + 9.2 Combine like terms: -9.2 + 9.2 = 0.0 0.0 + -0.2x = 2.4 + 9.2 -0.2x = 2.4 + 9.2 Combine like terms: 2.4 + 9.2 = 11.6 -0.2x = 11.6 Divide each side by '-0.2'. x = -58 Simplifying x = -58
| x^2+9x=22 | | (3x+5)(5x+7)=y | | 2z^2+z+5=0 | | 6k^2=18 | | 2+2(2+2)*2= | | -3t^2(5t^7)= | | x^2+1=3x^2-13 | | x^3(x^5)= | | 2=-3a(3-6) | | 7=6q+8 | | -2(4-c)=6c | | cx^2+2cx+4c=0 | | 2(x+x+2)=3x-13 | | 4(g+7)=-64 | | -4(5p+3)-38=5(3p+4) | | 4x+4=3x-13 | | 0=-6(y+4) | | -2+3=x | | -2-3=x | | 0=y-11-2y | | 6(y+1)+2(3-y)=7y | | x-7-4x=-25 | | x=4(4+8)+2(8-4) | | 5e-e+8=0 | | -8x=136 | | (-6)k-13=83 | | 5(2x-3)-(x+9)=21 | | 8(7-y)=6(y+9)+2 | | 16g-11g+15=0 | | 5(4x-6)+30= | | 2(7-w)=2-5w | | 5(4x-6)+30=0 |